Galectin-3, transforming growth factor beta 1, and brain natriuretic peptide in cardiac remodeling under hyperlipidemic and hyperglycemic stress - Hina Patel; Angelie Pathak; Resmi Rajalekshmi; Brian David; Devendra K. Agrawal (Molecular and Cellular Biochemistry, 2026)
Hyperlipidemia (HYL) and hyperglycemia (HYG) directly drive pathological cardiac remodeling; however, the mechanisms by which these conditions differentially regulate profibrotic signaling and early stress‑response pathways in left ventricular (LV) myocardium remain poorly defined. This study investigated the expression and localization of galectin-3 (Gal-3), transforming growth factor-β1 (TGF-β1), and brain natriuretic peptide (BNP) in a Yucatan miniswine model of HYL and HYG. Female Yucatan miniswine were assigned to normal control, HYL (high-cholesterol diet), or HYG (high-fat/high-carbohydrate diet plus low dose streptozotocin) groups ( n = 6/group) for 8-weeks, and LV tissue was assessed by histology, qRT-PCR, Western blot, and immunohistochemistry. Both metabolic conditions induced cardiomyocyte hypertrophy and interstitial fibrosis, with more diffuse collagen deposition in HYG myocardium. qRT-PCR demonstrated upregulation of Gal-3, TGF-β1, and BNP relative to controls, with transcript levels positively correlating with circulating glucose concentration. Western blot analysis showed relatively greater active TGF-β1 signal in HYL myocardium and greater latent precursor accumulation in HYG myocardium, suggesting condition-associated differences in TGF-β1 regulation. Immunohistochemistry demonstrated perivascular Gal-3 localization, cytoplasmic and perinuclear TGF-β1 immunoreactivity in cardiomyocytes, and BNP immunoreactivity predominantly within subendocardial Purkinje fibers, with increased staining intensity in metabolically stressed groups compared with controls. Collectively, these findings suggest that HYL and HYG are associated with overlapping but distinct patterns of Gal-3, TGF-β1, and BNP expression during metabolic cardiac remodeling. The Gal-3/TGF-β1 axis may represent a shared profibrotic pathway, whereas BNP may reflect a compensatory stress response whose functional significance requires further mechanistic validation.